Antitumor effect of anti-vascular therapy with STING agonist depends on the tumor microenvironment context - Czapla, Justyna; Drzyzga, Alina; Matuszczak, Sybilla; Cichoń, Tomasz; Rusin, Marek; Jarosz-Biej, Magdalena; Pilny, Ewelina; Smolarczyk, Ryszard (Frontiers in Oncology, 2023)
Introduction: Targeting tumor vasculature is efficient weapon to fight against cancer however activation of alternative pathways to rebuild the disrupted vasculature leads to rapid tumor re-growth. Immunotherapy that exploit host immune cells to elicit and sustain potent anti-tumor response has emerged as one of the most promising tools for cancer treatment, yet many treatments fail due to developed resistance mechanisms. Therefore, our aim was to examine whether combination of immunotherapy and anti-vascular treatment will succeed in poorly immunogenic, difficult-to-treat melanoma and triple negative breast tumor models. Methods: Our study was performed on B16-F10 melanoma and 4T1 breast tumor murine models. Mice were treated with stimulator of interferon genes (STING) pathway agonist (cGAMP) and vascular disrupting agent combretastatin A4 phosphate (CA4P). Tumor growth was monitored. The tumor microenvironment (TME) was comprehensively investigated using multiplex immunofluorescence and flow cytometry. We also examined if such designed therapy sensitizes investigated tumors models to immune checkpoint inhibitor (anti-PD-1). Results: The use of STING agonist cGAMP as monotherapy was insufficient to effectively inhibit tumor growth due to low levels of STING protein in 4T1 tumors. However, when additionally combined with an anti-vascular agent, a significant therapeutic effect was obtained. In this model, the obtained effect was related to the TME polarization and the stimulation of the innate immune response, especially activation of NK cells. Combination therapy was unable to activate CD8+ T cells. Due to the lack of PD-1 upregulation, no improved therapeutic effect was observed when additionally combined with anti-PD-1 inhibitor. In B16-F10 tumors, highly abundant in STING protein, cGAMP as monotherapy was sufficient to induce potent anti-tumors response. In this model, the therapeutic effect was due to the infiltration of TME with activated NK cells. cGAMP also caused the infiltration of CD8+PD-1+ T cells into TME, hence additional benefits of using PD-1 inhibitor were observed. Conclusions: The study provides pre-clinical evidence for a great influence of the TME on the outcome of applied therapy, including immune cells contribution and ICI responsiveness. We pointed the need of careful TME screening prior anti-tumor treatments to achieve satisfactory results.